NEK ABU BAKONGAN: BIOGRAFI SEORANG TOKOH ULAMA DARI BAKONGAN KABUPATEN ACEH SELATAN (1905 - 2011) - Khairuddin ,; Anwar Yoesoef; Mawardi . (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2018)
ABSTRACT The research, entitled "Nek Abu Bakongan: Biography of a Ulama Leader from Bakongan, South Aceh District (1905 - 2011)", aims to: (1) reconstruct the Biography of Nek Abu Bakongan (1905 - 2011), (2) explain how thought and the role of Nek Abu Bakongan in developing Islam Religious Education in Aceh especially Bakongan, and (3) explaining the factors that influenced the thought of Nek Abu Bakongan. This study uses a qualitative approach and historical method that consists of five steps: theme selection, heuristics, verification, interpretation and historiography. Data collection by observation, interview, documentation and literature study. Based on the results of research could seen that conclusion : (1) Abuya Tgk. Shaykh. H. Adnan Bin Mahmud or better known as Nek Abu Bakongan was born in March 1905 in Suak Beurembang, Manggeng Sub-district, South Aceh District, is a kharismatic scholar of Aceh. Education obtained by Nek Abu Bakongan especially is Islamic Religious Education, both about the science of fiqh, monotheism, hadith, tasawuf and others. During his lifetime, Nek Abu Bakongan has contributed a lot in Islamic education, such as establishing mosques, dayah / pesantren, spreading Islamic preaching and writing works of Islamic nuance, (2) Nek Abu Bakongan's thought in developing Islamic religious education in Bakongan, in the mosque, dayah, pesantren and through lectures and papers, and (3) the thought of Nek Abu Bakongan influenced by family factor (father) as well as place pengajiannya namely dayah Ahlussunnah Waljama'ah.Keywords: Biography, Nek Abu Bakongan.